Experimental and numerical analysis for the post-buckling behavior of stiffened composite panels with impact damage. (1st December 2015) - Wang, X.M.; Cao, W.; Deng, C.H.; Wang, P.Y.; Yue, Z.F.
Abstract: The paper deals with post-buckling experimental investigation on stiffened composite panels with pre-damage. Two panels with four equally spaced stiffeners were manufactured and tested. The damage was implemented at the vulnerable stiffener edge. Attempts were made to obtain the buckling load, ultimate carrying capacity and other wanted structure properties. A numerical methodology for the post-buckling behavior analysis of pre-damaged panels was also presented. The load-shortening curves of numerical results were compared with that of experimental results, and it gave a good prediction up to the onset of buckling and the collapse load. Experimental strain analysis indicated that the outer sublaminate at the damage location was buckling before the global buckling occurred, and the post-failure views also showed that the multiple delaminations and the unstable buckling took place at the damage site firstly and transversely propagated. It was validated by the simulated damage patterns which showed that the compression matrix failure and the shear failure in the impact site led to the collapse of the panel.